Burner based thermal management approach utilizing in-exhaust burner technology with a CDA equipped engine - Zavala, Bryan Abel; McCarthy, James E.; Harris, Thomas (Frontiers in Mechanical Engineering, 2023)
Commercial vehicles require fast aftertreatment heat-up to move the SCR catalyst into the most efficient temperature range to meet upcoming NOX regulations while minimizing CO2. One solution to this challenge is to add a fuel burner upstream of the conventional heavy-duty diesel aftertreatment system. The focus of this paper is to further reduce NOX and CO2 relative to a previous study of a burner system, to reside safely with 2027 emissions levels. This was accomplished by pairing the burner system with cylinder deactivation on the engine and/or a light-off SCR sub-system. A system solution is demonstrated using a heavy-duty diesel engine with an aged aftertreatment system targeted for 2027 emission levels using various levels of controls. The baseline layer of controls includes cylinder deactivation to raise the exhaust temperature more than 100° C in combination with elevated idle speed to increase the mass flowrate through the aftertreatment system. The combination of operating the fuel burner, cylinder deactivation and elevated idle speed (during cold start) allows the aftertreatment system to heat up in a small fraction of the time demonstrated by today’s systems. Performance was quantified over the cold FTP, hot FTP, low load cycle (LLC) and the U.S. beverage cycle. The improvement in NOX reduction and the CO2 savings over these cycles are highlighted.